The role of tacstd-2 level in hepatitis C patients (controlled clinical research). Issue 1 (1st January 2019) - Sahin, Memduh; Yetim, Aylin; Ates, Fehmi
ABSTRACT: Hepatitis C virus is one of the leading causes of liver cirrhosis and hepatocellular carcinoma. The tumor-associated calcium signal transducer 2 (Tacstd-2) molecule is thought to be involved in the expression of a number of molecules that facilitate transport of hepatitis C into the cell. The aim of this study was to investigate Tacstd-2 concentrations in hepatitis C patients, with and without cirrhosis, and compare with uninfected controls. Sixty-one hepatitis C patients and twenty-nine control (hepatitis C antibody negative patients with dyspeptic complaints) cases were recruited between 2014 and 2016. Tacstd-2 concentrations in all hepatitis C and control patients were measured and compared. In addition, cirrhotic and non-cirrhotic hepatitis C patients were compared in terms of Tacstd-2 concentration, and comparison was made between patients with high and low concentrations of Tacstd-2. The mean Tacstd-2 concentration of patients with Hepatitis C was 691.2 ± 473.3 ng/U was significantly higher (p = 0.043) than in the healthy control group (524 ± 290.1 ng/U). Although the Tacstd-2 value was higher in cirrhotic than the non-cirrhotic patient group, the difference was not statistically significant (p = 0.78). Liver transferase concentrations were higher in hepatitis C patients with a Tacstd-2 concentration <500 ng/U compared to those with a Tacstd-2 concentration >500 ng/U. In patients with hepatitis C, Tacstd-2 level was detected at higher serum concentrations than healthy individuals. The introduction of hepatitis C virus into the cell can be relatively easy in people with a higher serum concentration of Tacstd-2.